Analisis gaya kepemimpinan transformasional terhadap kinerja karyawan yang dimediasi komitmen kerja - Rahmad Hidayat; Endi Sarwoko; Andi Nu Graha (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2020)
The purpose of this study was to determine the effect of transformational leadership on employee performance and to analyze the mediating role of work commitment. This research is a type of quantitative research, using a questionnaire arranged with a 5 point Likert scale. The research variables consisted of transformational leadership as an exogenous variable, employee performance as an endogenous variable, and work commitment while the mediating variable. The research sample was 80 employees of PT. Kalbe Farma, Tbk. The data analysis technique uses path analysis. The results showed that transformational leadership has a direct effect on employee performance. Other findings indicate that work commitment acts as a partial mediator of the relationship between transformational leadership and employee performance. Future research can develop research by including the role of organizational culture as a factor influencing commitment and performance.